Walking for leisure among adults from three Brazilian cities and its association with perceived environment attributes and personal factors - Gomes, Grace A. O. [UNESP]; Reis, Rodrigo S.; Parra, Diana C.; Ribeiro, Isabela; Hino, Adriano A. F.; Hallal, Pedro C.; Malta, Deborah C.; Brownson, Ross C. (Biomed Central Ltd., 2011)
Background: Walking is a popular form of physical activity and a convenient option to prevent chronic diseases. However, most of the evidence on this topic derives from high-income countries and little is known about walking patterns and its association with environmental features in low and middle income countries.Objectives: To describe walking for leisure and to identify its association with perceived environment and personal factors among residents of three state capitals from different regions of BrazilMethods: Cross sectional phone surveys were conducted in Recife, Curitiba and Vitoria (n = 6,166) in 2007, 2008 and 2009 respectively. Physical activity was measured using the leisure-time sections of the long version of the International Physical Activity Questionnaire (IPAQ). Perceived environment characteristics were assessed using a modified version of the Neighborhood Environment Walkability Scale (NEWS). Multivariable analysis tested the associations between walking for leisure and perceived environment characteristics across the cities using logistic regression.Results: The proportions of respondents meeting physical activity recommendations through walking for leisure were 9.6%, 16.0% and 8.8% in Curitiba, Recife and Vitoria, respectively. Engaging in 150 min/wk or more of walking for leisure was significantly associated with younger age, higher education, better self-rated health and with lack of sidewalks on nearby streets. We did not find positive associations between walking for leisure and traffic conditions and safety related to cycling/walking during the day or night.Conclusion: Most environmental features were not associated with walking for leisure. Personal factors were stronger predictors of walking for leisure as compared with perceived environment factors.